Life during the Renaissance - Netzley, Patricia D. (San Diego, CA : Lucent Books, 1998)
Describes the history, culture, and life of people living during the Renaissance.
Includes bibliographical references (p. 85-91) and index.
Keywords: Renaissance -- Juvenile literature; Renaissance